MODELING OF STORM WATER DRAINAGE SYSTEM FOR OBUBRA LOCAL GOVERNMENT AREA, CROSS RIVER STATE OF NIGERIA (FUDMA JOURNAL OF SCIENCES, 2024)
A model was developed for the Obubra catchment and subsequently applied in the study of the catchment basin. The model developed gave a multiple regression correlation of 0.994 at a significance level of 0.05. The model was calibrated using the first ten (10) set of values and a correction of 0.995 was obtained and was further verified using the second set of ten (10) values which gave a correlation of 0.995. the model was also validated using velocity- area method for water flow measurement having a relationship as Q= AV with a correlation of 1.0. Although, studies conducted in different areas have shown that a hundred percent (100%) success may not always be achieved in the urban environment yet, their damaging effects can be mitigated through management measures that can carefully designed by government or affected communities. Adequate constitution and routine maintenance of drainage channels be made, ensuring that the velocity satisfies the minimum requirement.
Keywords: discharge; drainage; modeling; storm water; urbanization